Interplay between Metal Ions and Nucleic Acids - Sigel, Astrid; Sigel, Helmut; Sigel, Roland K. O.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
The Metal Ions in Life Sciences series links coordination chemistry and biochemistry in their widest sense and thus increases our understanding of the relationship between the chemistry of metals and life processes. The series reflects the interdisciplinary nature of Biological Inorganic Chemistry and coordinates the efforts of scientists in fields like biochemistry, inorganic and coordination chemistry, molecular and structural biology, enzymology, environmental chemistry, physiology, toxicology, biophysics, pharmacy, and medicine. Consequently, the volumes are an essential source for researchers active in these and related fields as well as teachers preparing courses, e.g., in Bioinorganic Chemistry. MILS-10: Interplay between Metal Ions and Nucleic Acids provides in an authoritative and timely manner in 12 stimulating chapters, written by 24 internationally recognized experts from 8 nations, and supported by nearly 1500 references, about 20 tables, and 125 illustrations, many in color, a most up-to-date view on metal ion-nucleic acid interactions; the characterization of which is covered in solution and in the solid state. The volume concentrates on modern developments encompassing topics in the wide range from G-quadruplexes via DNAzymes, catalysis at the DNA scaffold, and metal-mediated base pairs to peptide nucleic acids (PNAs) being thus of relevance, e.g., for chemistry and nanotechnology but also for molecular biology and (genetic) diagnostics. The Editors Astrid Sigel, Helmut Sigel and Roland K. O. Sigel have long-standing interests in Biological Inorganic Chemistry. They published on metal ion interactions with nucleotides and nucleic acids and on related topics, and edited previously 44 volumes in the series Metal Ions in Biological Systems.
Keywords: Life sciences; Science (General).; Analytical biochemistry; Biotechnology; Chemistry, inorganic; Nucleic acids; Science -- Study and teaching; Life Sciences; Nucleic Acid Chemistry; Analytical Chemistry; Inorganic Chemistry; Biotechnology; Science, general; Science Education